Buckwheat self-assembling peptide-based hydrogel: Preparation, characteristics and forming mechanism. (April 2022) - Yu, Mengru; Lin, Shenzhu; Ge, Rui; Xiong, Chunyu; Xu, Linlin; Zhao, Mengting; Fan, Junfeng
Abstract: The synthetic self-assembly peptides are the main building blocks for the multifunctional hydrogels, but they have safety-related issues. However, the generation of self-assembly peptides from the plant-sourced proteins has not been attempted. This study aimed to demonstrate a scalable mild enzymatic approach for generating peptides (∼3.4 kDa) with robust hydrogel-forming capacity from buckwheat proteins. The peptides produced using this method exhibited a smooth and uniform micromorphology and high self-aggregation ability, and their hydrogels presented a porous texture and remarkable rheological properties. Further studies showed that the hydrophobic aggregation and the interchange of sulfhydryl groups and disulfide bonds, in particular hydrogen bonding, dominated the formation of peptide hydrogels. Proteomics analysis demonstrated regularly alternating and representative amino acid compositions of the self-assembly peptides responsible for potent hydrogel formation. The findings offered opportunities for the use of natural peptide-based hydrogels in a range of applications that relied on their synthetic counterparts. Graphical abstract: Image 1 Highlights: Proteolysis of natural protein can produce self-assembly peptides (BSP). BSP can self-assemble to robust hydrogel without any toxic covalent cross-linkers. Intermolecular forces, especially H-bonding, drive the formation of BSP hydrogel. BSP has the typical molecular features responsible for potent hydrogel formation. Natural peptide is alternative as building blocks for the multifunctional hydrogel.